2000
DOI: 10.1086/315262
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated withHelicobacter pyloriInfection by acagA‐Positive Strain in Children

Abstract: Although infection with a cagA-positive Helicobacter pylori strain is considered a risk factor for the development of duodenal peptic ulcer in adults, this association has not been demonstrated in children. The presence of cagA was investigated by polymerase chain reaction in H. pylori strains isolated from 27 children with duodenal ulcer and 53 without duodenal ulcer. All patients (100%) with duodenal ulcer and 33 (62.3%) without ulcer were colonized by a cagA-positive strain (P=.00007). A cagA-positive statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
3
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 31 publications
5
55
3
6
Order By: Relevance
“…Analysis of the different diseases showed a higher frequency of the cagA gene in H. pylori-positive patients with duodenal ulcer compared to patients with gastritis, gastric ulcer and gastric cancer. Queiroz et al (24) found that, in Brazil, 95.0% and 62.3% of strains isolated from children with and without duodenal ulcers are cagA-positive, respectively. Other studies have reported a higher frequency of the cagA gene in H. pyloripositive patients with peptic ulcer and gastric cancer (17,33,38) .…”
Section: Frequency Of Different Genotypes In Patients With Gastrointementioning
confidence: 99%
“…Analysis of the different diseases showed a higher frequency of the cagA gene in H. pylori-positive patients with duodenal ulcer compared to patients with gastritis, gastric ulcer and gastric cancer. Queiroz et al (24) found that, in Brazil, 95.0% and 62.3% of strains isolated from children with and without duodenal ulcers are cagA-positive, respectively. Other studies have reported a higher frequency of the cagA gene in H. pyloripositive patients with peptic ulcer and gastric cancer (17,33,38) .…”
Section: Frequency Of Different Genotypes In Patients With Gastrointementioning
confidence: 99%
“…The difference in cagA prevalence between the two patient groups may be due to other virulence-associated genes that are associated with the presence of the cagA gene. One suggestion by a previous report stated that bacterial binding to the fucosylated blood group antigen Lewis b (Le b ) is coded by the babA2 gene and is associated with the presence of the cagA gene [30]. Thus, differences in the prevalence of cagA between the two patient groups may depend on other factors such as the level of Le b expression in biliary and gastric cells.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-two (16.5%) H. pylori-positive children had DU. Among them, 52 were included in other studies (6,7).…”
Section: Methodsmentioning
confidence: 99%
“…Because VacA high producer H. pylori strains are also cagA-positive and VacA/cagApositive strain is associated with DU in children in certain populations, cagA was included in the logistic model as the virulence H. pylori marker (6).…”
mentioning
confidence: 99%